The scaler mode in the Pierre Auger Observatory to study heliospheric modulation of cosmic rays - Dasso, Sergio Ricardo (2012)
The impact of the solar activity on the heliosphere has a strong influence on the modulation of the flux of low energy galactic cosmic rays arriving at Earth. Different instruments, such as neutron monitors or muon detectors, have been recording the variability of the cosmic ray flux at ground level for several decades. Although the Pierre Auger Observatory was designed to observe cosmic rays at the highest energies, it also records the count rates of low energy secondary particles (the scaler mode) for the self-calibration of its surface detector array. From observations using the scaler mode at the Pierre Auger Observatory, modulation of galactic cosmic rays due to solar transient activity has been observed (e.g., Forbush decreases). Due to the high total count rate coming from the combined area of its detectors, the Pierre Auger Observatory (its detectors have a total area greater than 16,000 m2 ) detects a flux of secondary particles of the order of 108 counts per minute. Time variations of the cosmic ray flux related to the activity of the heliosphere can be determined with high accuracy. In this paper we briefly describe the scaler mode and analyze a Forbush decrease together with the interplanetary coronal mass ejection that originated it. The Auger scaler data are now publicly available.